2013
DOI: 10.4238/2013.october.22.2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular authentication of multi-species honeysuckle tablets

Abstract: ABSTRACT. Authenticating multi-species original raw materials in commercial formulations is difficult. Jin Yin Hua and Shan Yin Hua, both classified as raw honeysuckle materials in the Chinese Pharmacopoeia, are used in various medicines. Differentiating one variety from another is difficult based on chemical analysis. We developed molecular authentication of multi-species original honeysuckle in 3 brands of commercial tablets using allele-specific PCR. All 3 tablets contained both Jin Yin Hua and Shan Yin Hua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For certain species, an even higher frequency of substitution appears in turmeric powder (20%) 5 , Ginkgo biloba leaf (24.3%) 6 , black cohosh dietary supplements (25%) 7 , commercial teas (33%) 8 , and Rhodiola decoctions (60%) 9 . Similar to the situation for herbal dietary supplements, substitutions and counterfeits have also been documented in patented Chinese drugs 10 11 12 . Moreover, due to their heterogeneous origins and differences in preparation methods, the substitutes for patented Chinese drugs may be present at higher levels than indicated by current estimates.…”
mentioning
confidence: 81%
“…For certain species, an even higher frequency of substitution appears in turmeric powder (20%) 5 , Ginkgo biloba leaf (24.3%) 6 , black cohosh dietary supplements (25%) 7 , commercial teas (33%) 8 , and Rhodiola decoctions (60%) 9 . Similar to the situation for herbal dietary supplements, substitutions and counterfeits have also been documented in patented Chinese drugs 10 11 12 . Moreover, due to their heterogeneous origins and differences in preparation methods, the substitutes for patented Chinese drugs may be present at higher levels than indicated by current estimates.…”
mentioning
confidence: 81%
“…Jin Yin Hua possesses biological and pharmaceutical properties such as antioxidant, antiangiogenic, antipyretic, antidiabetic, antibacterial, anti-inflammatory, antitumoral, antiviral, antiangiogenic, hepatoprotective, and antinociceptive activities. 37 Studies have shown its chemical components to have inhibitory actions on viruses including adenovirus, mice influenza virus, respiratory syncytial virus, herpes simplex virus 1 (HSV1), coxsackievirus B3, and parainfluenza. 38…”
Section: Lonicerae Japonicae ( J In Yín Hu A)mentioning
confidence: 99%
“…Xu et al (2015) used SSR technology to construct SSR fingerprints in Excel format for six different types of L. japonica, providing the earliest data support for variety identification. In addition, there have been no studies on the identification of Lonicera varieties based on DNA molecular markers (Jiang et al, 2013). The SNP molecular marker technology used in this study refers to the DNA sequence polymorphism caused by the variation of a single base in the genomic DNA sequence (Gazendam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%